USING THE SUSTAINABLE BALANCED SCORECARD TO EVALUATE INVESTMENT IN INFORMATION TECHNOLOGY - Sadeq Dhahir Farhan Alzaidi (Scholars Digest Publishing, 2025)
The research aims to demonstrate the impact of using the sustainable balanced scorecard on the effectiveness of evaluating investment in information technology, and its ability to improve the evaluation of investment in information technology. The descriptive analytical approach was relied upon, and the questionnaire was adopted as a tool for collecting data. The questionnaire was distributed to a sample of 50 employees in the Bank of Baghdad, and the valid items for analysis amounted to 45 items. The analysis of the collected data was carried out according to the program SPSS statistical analysis according to appropriate tests, and the results concluded that there is a statistically significant effect of using the sustainable balanced scorecard on the effectiveness of evaluating investment in information technology.
Keywords: Sustainable balanced scorecard, Information technology.